Legal Analysis of the Forestry Sector from the Perspective of Legislation in Indonesia - Warsito; Rahayu Subekti (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This research aims to identify government involvement in community activities using legal instruments in the form of permits. However, the permit does not end at the approval stage. Once permission is given, supervision is required, so clear rules are needed regarding who must be supervised. The research method used is normative legal research with a conceptual approach, namely the study of legal concepts such as legal sources, legal functions and legal systems. This research method is used to find conflicting supervisory regulations in the forestry sector. Others, namely Law Number 41 of 1999 concerning Forestry, Law Number 32 of 2009 concerning Environmental Protection and Management, and Law Number 23 of 2014 concerning Government Areas which may have different legal interpretations. In order for legal products to be a means of achieving sustainable forest development, these products must be designed in accordance with the nature of the forest itself. In other words, sustainable forest development must be based on will, awareness and political decisions. Then this will have no effect. This does not only apply to the current generation, but also to future generations.